2013
DOI: 10.1136/sextrans-2013-051097
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bio-behavioural HIV surveillance surveys among female sex workers in Sudan, 2011–2012

Abstract: ObjectivesTo assess HIV and syphilis prevalence, HIV-related behaviours and testing for HIV in female sex workers (FSW) in Sudan.DesignBio-behavioural surveys using respondent-driven sampling were carried out among FSW in the capital cities of 14 states in Sudan in 2011–2012. HIV and syphilis testing was done by rapid tests.Results4220 FSW aged 15–49 years were recruited. The median age of recruited women varied from 21 to 28 years per site. The highest HIV prevalence was measured at two sites in the eastern z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 10 publications
2
50
1
1
Order By: Relevance
“…In this study, 20.0% (142/710) of FSW study participants sampled in Maseru and Maputsoe, Lesotho were sexually exploited as children. This is comparable to estimates from Kenya [15,39], Mozambique [14], and Sudan [40]. HIV prevalence was extraordinarily high among this sample of FSW in Lesotho compared to that reported in other settings.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, 20.0% (142/710) of FSW study participants sampled in Maseru and Maputsoe, Lesotho were sexually exploited as children. This is comparable to estimates from Kenya [15,39], Mozambique [14], and Sudan [40]. HIV prevalence was extraordinarily high among this sample of FSW in Lesotho compared to that reported in other settings.…”
Section: Discussionsupporting
confidence: 79%
“…In spite of similar exposure to HIV infection in urban and rural areas, the majority of the infected women were of urban residence. This because in urban areas there is good access to the information and knowledge about HIV and in Sudan there are 143 voluntary counselling and testing sites, which are located mainly in urban areas (Elhadi et al 2013). In consistent with our findings, it is proved that HIV can lead to adverse pregnancy outcomes such as preterm birth and anaemia (Levine et al 2001).…”
Section: Human Immune Deficiency Virus Infection Among Women Represensupporting
confidence: 85%
“…Moreover, the majority of new HIV infections in Sub-Saharan Africa occur in the women of reproductive age (UNAIDS 2010). There is limited epidemiological data on HIV infected people in Sudan (Elhadi et al 2013), thus the current study was conducted on all pregnant women (during their antenatal care and in labour ward) attending Gadarif Maternity Hospital (Eastern Sudan) from January 2009 to December 2013 to investigate the maternal characteristics, pregnancy outcomes and estimate of maternal to child transmission of HIV among HIV infected women. All pregnant women in the hospital were offered HIV voluntary counselling and testing (VCT) free of charge.…”
Section: Human Immune Deficiency Virus Infection Among Women Represenmentioning
confidence: 99%
“…A recent study of FSWs in Johannesburg, South Africa, showed that 21% of participating women had antibodies that suggested past or current infection and 3% had active (infectious) infection 28 . Another study of FSWs in 14 zones in Sudan showed high seroprevalence (median 4.1%), with the highest value of 8.9% in the eastern zone of the country 29 . A large study of >1,000 FSWs in Kampala, Uganda, showed 21% were seropositive for syphilis and 10% had active infection 30 .…”
Section: Epidemiologymentioning
confidence: 95%